Ameloblastoma - An enigma - Jiji George; Mala Kamboj (Elsevier, 2012)
Ameloblastoma remains an enigmatic group of oral tumors, inspite of being so frequently encountered and widely discussed. Out of the total ameloblastomas reported, 81% cases have been in the mandible, of which 70% are in the molar-ramus area. We report two cases of ameloblastoma with misguiding radiographic and clinical pictures, which made us ponder that common oral lesions are sometimes, the most tough and confusing to diagnose.